The Effect of The Perceived Mental Image on The Purchasing Behavior of Customers: An Exploratory Study of a Sample of Customers of Iraqi Private Bank - أحمد صبيح لفتة; منصورة بور ميري; سرمد عبد الله امانة; احمد عبد الله امانة; ثراء ليث محمد رضا (Iraqi Journal for Administrative Sciences, 2024)
This study was conducted with the aim of identifying the role of the perceived mental image in increasing the purchasing behavior of customers in the Iraqi banking environment. The current study gained its importance from the field importance of the application environment, which was represented by a group of Iraqi private banks in the Holy Governorate of Karbala - Iraq, as an applied field of study, the sample size was randomly determined, which amounted to (384) customers, which was suitable for statistical analysis using the questionnaire, which is the main tool according to a five-point Likert scale. The statistical program SPSS was used to conduct validity and reliability analyses, descriptive analyzes and test the study hypotheses. This study concluded with a set of results, the most prominent of which was that the perceived mental image with its dimensions plays an effective role in enhancing customers’ purchasing behavior for the services provided by these private banks.